2022
DOI: 10.7717/peerj.13729
|View full text |Cite
|
Sign up to set email alerts
|

Association between IL-1A and IL-1B gene polymorphisms with peri-implantitis in a Portuguese population—a pilot study

Abstract: Background Scientific evidence indicates that biological complications in dental implants tend to be concentrated in a subset of individuals, which seems to imply that the host response may play a determining role in implant success. Over the last few decades, several polymorphisms have been studied. Polymorphisms in the interleukin (IL) 1 gene cluster have been associated with periodontitis. There are some similar features in the sequence of immunopathological events in peri-implant and periodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Although we know MBL can be the first sign of PI, the final diagnosis must be confirmed by other clinical parameters (BOP, suppuration, increased PD) [ 2 ]. The absence on this relation matches the results obtained by other authors [ 8 , 9 , 32 ], which were also performed with similar and more up-to-date diagnostic criteria of PI.…”
Section: Discussionsupporting
confidence: 90%
“…Although we know MBL can be the first sign of PI, the final diagnosis must be confirmed by other clinical parameters (BOP, suppuration, increased PD) [ 2 ]. The absence on this relation matches the results obtained by other authors [ 8 , 9 , 32 ], which were also performed with similar and more up-to-date diagnostic criteria of PI.…”
Section: Discussionsupporting
confidence: 90%
“…Cardoso et al. ( 24 ) in a pilot study that included a sample of 20 subjects, found a possible relationship between the IL-1 genotype and peri-implantitis, although another larger study on 98 subjects found no differences in the IL-8 polymorphism between groups with peri-implantitis and healthy subjects ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biofilms together with the breakdown products of peri-implant bone tissue, in the case of peri-implantitis, appear to result in a local immune response in the infected tissue and the production of proinflammatory cytokines such as IL-1β, associated with the stimulation of fibroblasts, endothelial cells and osteoclasts ( 24 ). IL-6 also induces bone resorption and, moreover, acts synergistically together with IL-1β, and it has been shown that the levels of both cytokines in peri-implant gingivocrevicular fluid (PGF) are higher in areas with peri-implantitis than in healthy areas ( 25 ), although cytokine levels in healthy areas are not perfectly defined ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our research group carried out a pilot study in which we observed that although there were no statistically significant differences in the IL-1A -889 and IL-1B +3954 polymorphisms between the healthy and peri-implantitis groups, there was a trend towards a higher prevalence of genetic polymorphisms in the disease group [ 52 ]. The IL-1RN (VNTR) polymorphism was not assessed in that study.…”
Section: Discussionmentioning
confidence: 99%